2021
DOI: 10.1016/j.jinf.2021.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for lack of transmission by close contact and surface touch in a restaurant outbreak of COVID-19

Abstract: Background: Coronavirus disease 2019 (COVID-19) is primarily a respiratory disease that has become a global pandemic. Close contact plays an important role in infection spread, while fomite may also be a possible transmission route. Research during the COVID-19 pandemic has identified long-range airborne transmission as one of the important transmission routes although lack solid evidence. Methods: We examined video data related to a restaurant associated COVID-19 outbreak in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…In outbreak R2 and R1, the estimated quanta generation rate was 1023.4 h -1 and 557.6 h -1 , respectively, which is much higher than the estimated quanta generation rate of 79.3 h -1 in a restaurant outbreak, and 35.0 h -1 and 58.3 h -1 in a two buses outbreak in early 2020. Li et al, (2021 ; Zhang et al, 2021 ; Chau et al, 2021 ; Lam et al, 2020 ; Li et al, 2021 ; Ou et al, 2022) Although the quanta generation rate for the Omicron variant in R2 is 83.5% larger than that for the non-Omicron variant in R1, the secondary attack rate is much lower in R2 (3.4%) than in R1 (28.9%), suggesting that enhancement of indoor air dilution may mitigate the SARS-CoV-2 transmission.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In outbreak R2 and R1, the estimated quanta generation rate was 1023.4 h -1 and 557.6 h -1 , respectively, which is much higher than the estimated quanta generation rate of 79.3 h -1 in a restaurant outbreak, and 35.0 h -1 and 58.3 h -1 in a two buses outbreak in early 2020. Li et al, (2021 ; Zhang et al, 2021 ; Chau et al, 2021 ; Lam et al, 2020 ; Li et al, 2021 ; Ou et al, 2022) Although the quanta generation rate for the Omicron variant in R2 is 83.5% larger than that for the non-Omicron variant in R1, the secondary attack rate is much lower in R2 (3.4%) than in R1 (28.9%), suggesting that enhancement of indoor air dilution may mitigate the SARS-CoV-2 transmission.…”
Section: Discussionmentioning
confidence: 97%
“… Tang et al, (2021 ; Morawska et al, 2020 ; Conte et al, 2021) Dining places and bars were considered as the high-risk area for COVID-19 outbreaks as people may interact closely without wearing masks. Li et al, (2021 ; Zhang et al, 2021 ; Chau et al, 2021) In fact, social gathering with mask-off activities has been shown to increase the risk of SARS-CoV-2 transmission during the early phase of COVID-19 pandemic. Cheng et al, (2020) In Hong Kong, the first community outbreak of COVID-19 with superspreading event was attributed to the family gathering and dining in a commercial party room.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 97.0% and 89.3% of the students respectively believed that large droplet and short-range airborne transmission were possible SARS-CoV-2 transmission routes. Although some studies of indoor outbreaks have shown that long-range airborne transmission is a dominant route, especially in settings with poor ventilation [ 30 , 31 ], only 24.1% of the students believed that this was a possible route of SARS-CoV-2 transmission. The evidence has increasingly demonstrated that fomite transmission plays an insignificant role in the COVID-19 pandemic [ 32 ]; however, 50.9% and 36.0% of the students believed that SARS-CoV-2 could be transmitted via the short-range and long-range fomite routes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 98.0 and 91.8% of 1,499 HCWs believed that large-droplet and short-range airborne transmission, respectively, were possible SARS-CoV-2 transmission routes. Although some studies of indoor outbreaks have shown that long-range airborne transmission is a dominant route, especially in settings with poor ventilation (23,24), only 20.0% (300/1,499) of the HCWs believed that this was a possible route of SARS-CoV-2 transmission. Accumulating evidence has demonstrated that fomite transmission plays an insignificant role in SARS-CoV-2 transmission (25, 26); however, 66.5% (997/1,499) and 43.0% (645/1,499) of that HCWs believed that SARS-CoV-2 could be transmitted via the short-range and long-range fomite routes, respectively.…”
Section: Discussionmentioning
confidence: 99%